Controversies in Liver Transplantation Recent Challenges and Future Perspectives - Kumar Yadav, Dipesh (IntechOpen, 2023)
Liver transplantation is an exciting field that encompasses a wide range of research areas like transplant immunology, transplant pharmacology, transplant oncology, infectious diseases, cardiovascular diseases, and more. This book includes chapters on liver transplantation for acute and chronic liver failure, liver transplantation for alcoholic liver disease, and economic considerations of liver transplantation.